Teaching Game for Understanding in Physical Education: A Theoretical Framework and Implication - Balakrishnan, Malathi; Rengasamy, Shabeshan; Aman, Mohd Salleh (ATIKAN, 2011)
ABSTRACT: The primary purpose of the present study was to investigate the effects of Teaching Games for Understanding (TGfU) approach to improve studentsâ learning outcome of tactical game performance in physical education. By applying the constructivism learning theory, the study wants to investigate whether the students learning outcome in tactical game performance can be improved with the TGfU approach. The participants in this study were 10 years old primary physical education students. The Game Performance Assessment Instrument (GPAI) was used to measure students tactical understanding of game performance. The results of the validation studies showed that the instruments developed for the purposes of this project were valid indicators of tactical game performance. The ANCOVA results revealed that there was a significant difference between the students who were exposed to TGfU approach and students with traditional skill approach on the post-test (F [1, 69] = 248.83, p < .05). This result indicated that the experimental group with TGfU approach has significant main effects on student learning outcome compared to the traditional skill approach. The findings of this study showed that constructivism theory improved primary physical education students learning outcome in physical education.KEY WORD: Teaching games for understanding, constructivism, tactical understanding, and primary physical education.Â Â Â Â About the Authors: Malathi Balakrishnan is a Doctoral Candidate at the Department of Mathematics and Science Education, Faculty of Education UM (University of Malaya), Kuala Lumpur, Malaysia; Shabeshan Rengasamy, Ph.D. is a Senior Lecturer at the Department of Mathematics and Science Education, Faculty of Education UM; and Assoc. Prof. Dr. Mohd Salleh Aman is Director of Sport Centre at UM. They can be reached at: malathi@siswa.um.edu.my, shabesh@um.edu.my, and amanms@um.edu.myHow to cite this article? Balakrishnan, Malathi, Shabeshan Rengasamy & Mohd Salleh Aman. (2011). âTeaching Game for Understanding in Physical Education: A Theoretical Framework and Implicationâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.1(2) Desember, pp.201-214. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, ISSN 2088-1290.Chronicle of the article: Accepted (October 13, 2011); Revised (November 23, 2011); and Published (December 15, 2011).